(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
This study aims to determine the relationship between female leadership styles and reducing work stress in educational settings. As organizations increasingly recognize the importance of a healthy work environment, understanding the role of leadership, especially the role of women leaders, has become critical. This study seeks to identify specific leadership behaviors and styles displayed by women in educational leadership positions that contribute to reducing work stress among their subordinates. The current study uses the methodology of an analytical exploratory study to explore how women’s leadership initiatives within organizations contribute to alleviating the negative effects of work pressures. To achieve the objectives of the study, the researchers distributed a questionnaire to workers in the institutes and colleges of Al-Furat Al-Awsat Technical University. (260) responses were obtained and were analyzed using the program. Advanced statistics SmartPLS V.4 The study reached a set of conclusions, the most important of which is: Women leaders are more inclined towards making collaborative decisions, which enhances the feeling of inclusiveness and shared responsibility. This approach can contribute to creating a healthier work atmosphere and may reduce the tension associated with top-down leadership styles. A set of recommendations were also presented, the most important of which are: Encouraging women leaders to adopt comprehensive leadership styles that promote cooperation, open communication, and a sense of belonging among team members. . As well as emphasizing the importance of empathy and understanding individual needs and challenges to create a supportive work environment.